The role of expectation in music: from the score to emotions and the brain. Issue 1 (7th November 2013) - Tillmann, B.; Poulin‐Charronnat, B.; Bigand, E.
Abstract : Like discourse, music is a dynamic process that occurs over time. Listeners usually expect some events or structures of events to occur in the prolongation of a given context. Part of the musical emotional experience would depend upon how composers (improvisers) fulfill these expectancies. Musical expectations are a core phenomenon of music cognition, and the present article provides an overview of its foundation in the score as well as in listeners' behavior and brain, and how it can be simulated by artificial neural networks. We highlight parallels to language processing and include the attentional and emotional dimensions of musical expectations. Studying musical expectations is thus valuable not only for our understanding of music perception and production but also for more general brain functioning. Some open and challenging issues are summarized in this article. WIREs Cogn Sci 2014, 5:105–113. doi: 10.1002/wcs.1262 This article is categorized under: Psychology > Perception and Psychophysics